2022
DOI: 10.1371/journal.pone.0268093
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 infection and associated factors among Bangladeshi slum and non-slum dwellers in pre-COVID-19 vaccination era: October 2020 to February 2021

Abstract: Background Seroprevalence studies have been carried out in many developed and developing countries to evaluate ongoing and past infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Data on this infection in marginalized populations in urban slums are limited, which may offer crucial information to update prevention and mitigation policies and strategies. We aimed to determine the seroprevalence of SARS-CoV-2 infection and factors associated with seropositivity in slum and non-slum commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…The time period of sample collection was October 2020 to February 2021 for this study [23] . Another study with the similar time period, reported a weighted seroprevalence of 72.9% in Dhaka and 54.2% in Chattogram, respectively [24] . The overall national seroprevalence was found to be 30.4% in a different study [17] .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The time period of sample collection was October 2020 to February 2021 for this study [23] . Another study with the similar time period, reported a weighted seroprevalence of 72.9% in Dhaka and 54.2% in Chattogram, respectively [24] . The overall national seroprevalence was found to be 30.4% in a different study [17] .…”
Section: Discussionmentioning
confidence: 83%
“…Several seroprevalence studies have been conducted in Bangladesh at different time periods. The previous studies in Bangladesh were mainly conducted in Dhaka and Chattogram [23] , [24] , [25] , [26] , [27] , [28] . In this study,we had conducted a cross-sectional observational study to estimate the seroprevalence and antibody level of anti-SARS-CoV-2 IgG in children, unvaccinated and vaccinated adults in different regions of Bangladesh including Dhaka, Rajshahi, Jhenaidah, Bogura and Dinajpur after the delta wave surge.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as the study protocol has been adopted from WHO unity study, we did not include questions on non-pharmaceutical public health measures, for example, use of masks which can influence the population seroprevalence as reported by other studies in Bangladesh. 51 …”
Section: Discussionmentioning
confidence: 99%
“…Open access non-pharmaceutical public health measures, for example, use of masks which can influence the population seroprevalence as reported by other studies in Bangladesh. 51…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation